Enhanced lightweight and compromised-resilient image encryption for resource constrained environments - Abid Mehmood; Abdul Nasir Khan; Iynkaran Natgunanathan; Arslan Shafique; Iftikhar Ahmed Khan; Atta ur Rehman Khan (PLoS ONE, 2025)
The Internet is experiencing a significant increase in multimedia traffic volume, highlighting the growing importance of managing and securing multimedia content efficiently. Classical or traditional security solutions are suitable for those applications that have sufficient computing resources. However, the rise of IoTs and its applications opens new directions for researchers to provide lightweight security solutions. Many IoT applications send critical image data over the Internet, which requires adequate protection. Traditional security solutions are not suitable due to the resource-constrained nature of the environments. An effective security solution is necessary for such environments that balance lightweight design with strong security measures. Current research efforts in this area lack the ability to provide both secure and lightweight properties simultaneously. Therefore, a robust and lightweight cryptosystem is needed to secure the sensitive information of digital images. This research addresses the existing gap by proposing a lightweight and robust cryptographic system that encrypts digital data in less processing time without compromising security. The proposed image encryption technique is evaluated using security and performance measures, such as cipher processing time, histogram analysis, entropy, correlation, mean square error and sensitivity analysis. Moreover, the comprehensive analysis reveals the proposed image encryption technique effectively and collectively meets all the security and performance requirements compared to existing state-of-the-art lightweight image encryption techniques.